Growth, nutrition and biological fixation of nitrogen in mixed-species plantations of eucalypt with leguminous trees - Coelho, Selma Regina de Freitas; Gonçalves, José Leonardo de Moraes; Mello, Sergio Luis de Miranda; Moreira, Rildo Moreira; Silva, Eduardo Vinícius da; Laclau, Jean-Paul (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to assess interactions between species on the above and belowground growth, nitrogen uptake and biological nitrogen fixation (BNF) in mixed stands of Eucalyptus grandis and native leguminous N2-fixing trees. A complete randomized block design was installed with seven treatments and three blocks. Within the lines of the E. grandis seedlings, native leguminous N2-fixing trees – Peltophorum dubium, Inga sp., Mimosa scabrella, Acacia polyphylla, Mimosa caesalpiniaefolia – and one exotic leguminous plant, Acacia mangium, were intercropped. E. grandis was also solely planted. Mimosa scabrella and A. mangium were the legume trees that presented the highest growth. Although E. grandis showed a lower growth when combined with M. scabrella, this mixed-species stand exhibited the highest biomass accumulation. Eucalyptus grandis fine root densities (FRD) were 6–20 times higher than the FRD of the leguminous species in the upper soil layer (0–10 cm) 24 months after planting. The FRD of M. scabrella and M. caesalpiniaefolia in the 30–50 cm soil layer was higher than in the 10–30 cm layer. The d15N values of M. scabrella indicated that 90% of stocked N is derived from BNF.